(untitled) (Teología, 2016)
This work intends to think within the anthropological and theological horizon of the Encyclical. It tries to show the previousness of the community man-nature to any objectification, source of a certain philosophy and, through experiment, of the techno-scientific knowledge as human control over nature. The absolutization of this control is responsible for the dangers that threaten men in their confrontation with nature. This article shows that, alongside the activity and products of techno-science, there’s also beauty, which opens up possibilities that transcend the pure power over nature. In the light of these possibilities, a rapprochement to a more originary experience and language âˆ’religious, and especially, Christianâˆ’ might take place. But this requires an experience of faith capable of becoming a conceptual discourse, albeit insufficient and in need of constant renewal.